2022
DOI: 10.1016/j.drudis.2021.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Achieving end-to-end success in the clinic: Pfizer’s learnings on R&D productivity

Abstract: Over the past decade, Pfizer has focused efforts to improve its research and development (R&D) productivity. By the end of 2020, Pfizer had achieved an industry-leading clinical success rate of 21%, a tenfold increase from 2% in 2010 and well above the industry benchmark of ∼11%. The company had also maintained the quality of innovation, because 75% of its approvals between 2016 and 2020 had at least one expedited regulatory designation (e.g., Breakthrough Therapy). Pfizer’s Signs of Clinical Activity (SOCA) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
0
26
1
1
Order By: Relevance
“…Pfizer recently shared its learnings on increasing “end‐to‐end” success, which is currently almost twofold higher than the industry benchmark; whereas, in the previous decade it was consistently lagging behind its peers 3 . A major driver for this turnaround was a remarkable increase in phase II success, which is currently 50% higher than that of the rest of the industry 3,4 . The company has described the three building blocks behind its increased R&D productivity as follows: Biology: deeper understanding, emphasis on science, and sharper focus on specific therapeutic areas; Modalities: broadening the toolbox to a range of modalities beyond small molecules; and Decision making: incorporating more systematic and consistent use of quantitative metrics. …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Pfizer recently shared its learnings on increasing “end‐to‐end” success, which is currently almost twofold higher than the industry benchmark; whereas, in the previous decade it was consistently lagging behind its peers 3 . A major driver for this turnaround was a remarkable increase in phase II success, which is currently 50% higher than that of the rest of the industry 3,4 . The company has described the three building blocks behind its increased R&D productivity as follows: Biology: deeper understanding, emphasis on science, and sharper focus on specific therapeutic areas; Modalities: broadening the toolbox to a range of modalities beyond small molecules; and Decision making: incorporating more systematic and consistent use of quantitative metrics. …”
Section: Figurementioning
confidence: 99%
“…It has been suggested that 60% of all research and development (R&D) costs are due to attrition. 3 However, obtaining a single estimate of PoS is not trivial, since a variety of diverse elements need to be considered and integrated. Thus, the definition of "success" is multifactorial and includes technical, medical, regulatory, and commercial success.…”
Section: Probability Of Success In Drug Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these new drugs, the oral form nirmatrelvir/ritonavir provides the most promising therapeutic effect, an 89% reduction in the risk of hospitalization or death [ 7 , 9 , 12 ] ( Figure 1 ). Nirmatrelvir/ritonavir have been expected to change the course of the COVID-19 pandemic [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%